Interspecific and Intersexual Differences in the Chemical Composition of Floral Scent in Glochidion Species (Phyllanthaceae) in South China - Daihong Huang; Fuchen Shi; Minwei Chai; Ruili Li; Houhun Li (Journal of Chemistry)
Plants of the Glochidion (Phyllanthaceae) genus are pollinated exclusively by host-specific Epicephala (Gracillariidae) moths. Floral scent has been thought to play key role in the obligate pollination mutualism between Glochidion plants and Epicephala moths, but few studies have been reported about chemical variation in floral volatiles of Glochidion species in China. Floral volatiles of male and female flowers of five Glochidion species in south China were collected by dynamic headspace absorption technique and then were chemically analyzed by using gas chromatography-mass spectrometry. A total of 69 compounds were identified from floral scents of five investigated species. Glochidion hirsutum and G. zeylanicum showed no qualitative differences in floral scent, whereas there were clear variations of floral scent among other species (G. eriocarpum, G. daltonii, and G. sphaerogynum) and also they distinctly differed from these two species. Male flowers emitted significantly more scent than female flowers. Glochidion plants exhibited qualitative and quantitative differences in floral scent between two sexes of flowers. The findings suggest that the volatile variation of floral scent among Glochidion species reflects adaptations to specific pollinators. Sexual dimorphism in floral scent has evolved to signal alternative rewards provided by each sex to Epicephala moths.